From poverty reduction to mutual interests? The debate on differentiation in EU development policy - Svea Koch (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
The need to better adapt EU development policy to the varying levels of development of partner countries (“differentiation”) and the extent to which middle-income countries (MICs) should continue to receive EU aid have become contentious issues of the EU's new development policy agenda as well as in the negotiations on the next multi-annual financial framework. Due to the EU's mandate to ensure its global presence in all developing countries, development cooperation with MICs is more a question of how such cooperation should be framed rather than withdrawing from these countries. The Commission's proposal foresees ending bilateral aid allocations to 19 developing countries but continuing cooperation under thematic and regional programmes. Ongoing discussions between the Commission, Member States and the European Parliament have so far focussed mainly on the “right” criteria for such graduation and the extent to which specific countries should be exempt from the rule. So far, the EU has not presented a clear strategy of how exactly it aims to change its development programmes with this group of advanced developing countries, and has thus created some ambiguity on the actual implications of a differentiated approach. What are the strategic priorities and policy objectives of these new forms of cooperation? Will the EU continue to focus on poverty reduction or will the cooperation objectives shift to addressing regional and global development challenges? The debate on differentiation needs to be placed in the context of two interlinked challenges – both being of fundamental importance for the future direction of EU development policy: the phenomenon of continued poverty and rising inequality in countries that have generated fast economic growth; and the growing range of global challenges and the strategically important role of many MICs in securing global commons. With regards to the implications for EU developmentpolicy, there are two main conclusions: Tackling global poverty needs both better “technical” solutions for classifying countries and, on the political level, a better coordinated cross-country division of labour and joint EU strategy towards advanced developing countries; The EU needs to address the mismatch between partner country portfolio and development objectives. Due to its global presence, the EU is ideally placed to adopt a global rationale of development policy, in particular in its cooperation with MICs. This global outlook on development will increase the coordination challenges of EU development policy and other European external policies substantially. The EU's instrument framework – and in particular the Development Cooperation Instrument (DCI) – needs to be designed to allow for the continued funding of poverty reduction and social cohesion programmes in graduating countries. At the same time, it should make sufficient resources for the proposed “Global Public Goods” programme available to demonstrate a clear shift towards a global rationale of development policy.
Keywords: 330; Armut und Ungleichheit; Deutsche + Europäische + multilaterale Entwicklungspolitik